The Impact of Economic Growth and Financial Crisis on Islamic Financial Development in Terms of Size in Iran - Hacine Gherbi Elhachemi; Mohammad Azmi Othman (International Journal of Economics and Financial Issues, 2016)
This paper use empirical analysis to examine short run and long Iran's Islamic banking and financial market development in terms of size -growth-crisis nexus and identify the Granger causality relationship among them over the period of 1990Q1 to 2010Q4 for Islamic banking sector and over the period of 1994Q1 to 2012Q4 for Islamic financial market sector. This study utilizes the ARDL models and, this study is helpful for the investors, bankers and policy makers for formulating the future policy. In addition, this paper is a first attempt to study the relationship between Islamic financial size development in both of banking sector and financial market and economic growth without ignoring the potential causal link between Islamic financial development and financial crisis.The results shows that growth has a positive effect on Islamic financial size development, while financial crisis has significant negative effect contrary to the theory in Islamic republic of Iran. Keywords: Islamic, Banking, market, Growth, Crisis, Size, Development, Causality, Nexus, ARDL.